city of Al-Gharraf in the sixth and seventh centuries AH - Ali Ganem Chetheer (Thi Qar Arts Journal, 2025)
The importance of studying the city of Al-Gharraf in the sixth and seventh centuries AH lies in the fact that the subject is distinguished by its newly, as it was not highlighted in the Islamic era, and all the focus was directed towards (Wasit), expect the affiliated cities with it, including the city of Al-Gharraf, that did not study and attention enough, perhaps due to the rare of information, and this is the problem I faced in our study about Al-Gharraf. However, with the use of scientific analysis tools for texts, we can provide a picture of the history of this city at that time and explain its value, especially the scientific one.